1966
DOI: 10.1115/1.3625133
|View full text |Cite
|
Sign up to set email alerts
|

Momentum Transfer in Turbulent Separated Flow Past a Rectangular Cavity

Abstract: This paper presents results of an analytical and experimental investigation aimed at describing the turbulent momentum transfer mechanism in the separated-flow region of a rectangular cavity facing an oncoming turbulent boundary layer. A flow model of the mixing region in the slot postulated on the basis of eddy diffusion in free jets gives values of velocities and drag in good agreement with the measurements. The results further point to the significant effects exerted by the oncoming boundary layer on transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
12
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(17 citation statements)
references
References 0 publications
5
12
0
Order By: Relevance
“…It is believed that the high rate of energy dissipation, associated with form drag generated by the steps, contributes to strong turbulent mixing throughout the entire flow. Although the quantitative values of turbulence intensity are large (Tu ~ 100%), they are similar to turbulence measurements in separated flows past rectangular cavity (Haugen and Dhanak 1966), in wakes between large stones (Sumer et al 2001), in developing shear region of plunging water jets (Chanson and Brattberg 1998) and in pipe flows (Mudde and Saito 2001). Note that only the metrology of Mudde and Saito was comparable to the present signal processing technique.…”
Section: Air-water Velocity and Velocity Fluctuation Profilessupporting
confidence: 74%
“…It is believed that the high rate of energy dissipation, associated with form drag generated by the steps, contributes to strong turbulent mixing throughout the entire flow. Although the quantitative values of turbulence intensity are large (Tu ~ 100%), they are similar to turbulence measurements in separated flows past rectangular cavity (Haugen and Dhanak 1966), in wakes between large stones (Sumer et al 2001), in developing shear region of plunging water jets (Chanson and Brattberg 1998) and in pipe flows (Mudde and Saito 2001). Note that only the metrology of Mudde and Saito was comparable to the present signal processing technique.…”
Section: Air-water Velocity and Velocity Fluctuation Profilessupporting
confidence: 74%
“…The mechanism is very similar to cases shown in Fig. 8 in which the vortices have been observed widely in field and laboratory (Liu 2006;Hangen and Dhanak 1966;van Schijndel 1998;Schmidt 1990). In the experiment by Liu (2006), the nonzero velocity w was artificially generated and then, the circulation shown in Fig.…”
Section: ½31supporting
confidence: 61%
“…This flow behavior affects the incident boundary layer, i.e. skin friction coefficient, mean velocity profiles and turbulence intensity distribution [4][5][6][7][8][9]. Elavarasan et al [4] found an increase in u , the rootmean-square value of the streamwise velocity, just downstream of the cavity.…”
Section: Introductionmentioning
confidence: 96%